The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3847/1538-4357/ab0d7b
|View full text |Cite
|
Sign up to set email alerts
|

The Aemulus Project. III. Emulation of the Galaxy Correlation Function

Abstract: Using the N-body simulations of the AEMULUS Project, we construct an emulator for the non-linear clustering of galaxies in real and redshift space. We construct our model of galaxy bias using the halo occupation framework, accounting for possible velocity bias. The model includes 15 parameters, including both cosmological and galaxy bias parameters. We demonstrate that our emulator achieves ∼ 1% precision at the scales of interest, 0.1 < r < 10 h −1 Mpc, and recovers the true cosmology when tested against inde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
202
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 149 publications
(208 citation statements)
references
References 63 publications
6
202
0
Order By: Relevance
“…First, it is important to realise that a surrogate model such as Gaussian process emulation cannot perfectly reproduce the full forward-modelling approach. In the case of Zhai et al (2019), it was shown that emulator inaccuracies are roughly of the same order of magnitude as the typical observational uncertainties of the data. This has two important implications.…”
Section: Surrogate Modelmentioning
confidence: 87%
See 4 more Smart Citations
“…First, it is important to realise that a surrogate model such as Gaussian process emulation cannot perfectly reproduce the full forward-modelling approach. In the case of Zhai et al (2019), it was shown that emulator inaccuracies are roughly of the same order of magnitude as the typical observational uncertainties of the data. This has two important implications.…”
Section: Surrogate Modelmentioning
confidence: 87%
“…Finally, the predictionsD are used as training points for an emulator, most commonly a Gaussian process emulator, to predictD for arbitrary points in the cosmology and galaxy-halo parameter space without the need to re-run expensive simulations. The most extensive example of such an emulator approach in the context of the small-scale clustering of galaxies is the work of Zhai et al (2019) (also see Kwan et al 2015;Nishimichi et al 2018;Wibking et al 2019b). In this study, the authors constructed an emulator for the redshift-space clustering of galaxies in the BOSS CMASS survey.…”
Section: Surrogate Modelmentioning
confidence: 99%
See 3 more Smart Citations